Phytobezoar and duodenal ulcer as complication of Duodopa therapy in a patient affected by Parkinson's disease. (29th June 2018) - Cerrone, Paolo; Marchese, Michele; Pistoia, Maria Antonietta; Marini, Carmine
Abstract : Continuous duodenal infusion of levodopa/carbidopa intestinal gel (LCIG) is an established treatment to control motor fluctuations in Parkinson's disease. Duodenal infusion allows a steady absorption of the drug in the small bowel, reducing plasmatic fluctuations of levodopa. Some complications may occur during the treatment, often related to intrajejunal percutaneous endoscopic gastrostomy (PEG-J). We report a case of duodenal ulcer associated with a phytobezoar involving the end of jejunal probe, in a patient who underwent PEG-J for LCIG infusion. In the last 2 weeks, the patient suffered from abdominal pain and dyspepsia. Oesophagogastroduodenoscopy showed an ulcerative lesion of the duodenum due to traction of the jejunal tube; the end of the jejunal tube was wrapped in a phytobezoar. This case is interesting because of the extension of the ulcerative lesion due to PEG-J dislocation and because of the subtle symptoms associated with it.